Examining the Built Environment for Healthy Living via Virtual Street Audits. (June 2022) - Fifolt, Matthew; Mooney, Stephen J; Nabavi, Meena; Karimi, Maryam; Nassel, Ariann; McCormick, Lisa C
During the fall 2019 and spring 2020 semesters, 156 MPH students enrolled in the Integrative Learning Experience at the University of Alabama at Birmingham School of Public Health explored concepts of the built environment and health by auditing 2500 street segments in 4 urban neighborhoods in Birmingham, Alabama. In teams of 4 to 5, in-class and online students worked collaboratively to assess 63 built environment variables related to transportation, land use, advertisement, and neighborhood physical disorder. This type of "community assessment" is the first stage of the Evidence-based Public Health Framework and consistent with the applied nature of an MPH degree. Authors conducted secondary data analysis of final team assignments to demonstrate how students translated observations and ratings into practical recommendations for neighborhood improvements to promote physical activity. Students recommended improvements in neighborhood infrastructure and services, specifically: creating exercise space, providing outdoor exercise equipment, improving neighborhood safety, and cultivating a culture of health. The Integrative Learning Experience course encouraged students to use their knowledge and skills to prioritize recommendations to improve neighborhood conditions. Variable ratings and observations increased student awareness of the built environment and its potential to impact individual and community health. Moreover, the project helped students make connections between proximal outcomes, such as improving neighborhood walkability, and distal outcomes, such as improved health outcomes among residents. Finally, this project modeled for students the use of evidence-based strategies for making data-informed decisions, which are essential skills for new and emerging public health professionals.